2005
DOI: 10.1137/050625540
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Range of Bursting in a Model Respiratory Pacemaker Network

Abstract: A network of excitatory neurons within the pre-Bötzinger complex (pre-BötC) of the mammalian brain stem has been found experimentally to generate robust, synchronized population bursts of activity. An experimentally calibrated model for pre-BötC cells yields typical square-wave bursting behavior in the absence of coupling, over a certain parameter range, with quiescence or tonic spiking outside of this range. Previous simulations of this model showed that the introduction of synaptic coupling extends the burst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 75 publications
(79 citation statements)
references
References 32 publications
4
75
0
Order By: Relevance
“…Increasing g syn-e , however, pushes the homoclinic point to smaller h values, such that a larger g tonic-e is needed to attain the bursting-to-spiking transition ( Fig. 2; Best et al 2005). These findings can also be cast in terms of I NaP .…”
Section: How Synaptic Coupling Promotes Burstingmentioning
confidence: 88%
See 3 more Smart Citations
“…Increasing g syn-e , however, pushes the homoclinic point to smaller h values, such that a larger g tonic-e is needed to attain the bursting-to-spiking transition ( Fig. 2; Best et al 2005). These findings can also be cast in terms of I NaP .…”
Section: How Synaptic Coupling Promotes Burstingmentioning
confidence: 88%
“…Moreover, changes in g tonic-e and g syn-e induce complex variations in burst characteristics (Butera et al 1999b). The key to these results (Best et al 2005) is the observation that both g tonic-e and g syn-e affect the bifurcation structure of the pBC cell's fast subsystem. Consideration of a single self-coupled cell gives a first approximation to the effect of g syn-e .…”
Section: How Synaptic Coupling Promotes Burstingmentioning
confidence: 92%
See 2 more Smart Citations
“…Bifurcation structures of bursting oscillations in cells has been studied in detail Marhl 2003, 2007;), for example. Best et al studied a two-cell model network with synaptic coupling and they found that the square-wave bursting is replaced by the top hat bursting (also known as fold/fold cycle bursting) over a wide parameter range (Best et al 2005). The transition from bursting to spiking has been studied in a variety of neuronal models (Bi et al 2014;Duan et al 2012;Rinzel 1985;Izhikevich 2000;Jia et al 2012;Gu and Xiao 2014).…”
Section: Introductionmentioning
confidence: 99%